2015
DOI: 10.1111/cdep.12137
|View full text |Cite
|
Sign up to set email alerts
|

How Economic Downturns Affect Children's Development: An Interdisciplinary Perspective on Pathways of Influence

Abstract: ABSTRACT-To understand how economic downturns affect children's development, scholars have concentrated on how parents' loss of a job affects children's well-being, but have largely ignored the potential effects of downturns on children whose parents remain employed. In this article, we review research across disciplines to demonstrate that economic downturns should be conceptualized as a community-level event that affects all children in a community, not just those whose parents have lost jobs. We focus on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 48 publications
1
21
0
1
Order By: Relevance
“…Our findings provide further evidence for the contention that the Great Recession may have adversely affected parents, even if they themselves did not experience economic hardship (Gassman-Pines, Gibson-Davis, & Ananat, 2015). Indeed, our results indicate that widespread economic uncertainty—as measured by the CSI and local unemployment rates—may have increased mothers’ harsh parenting practices.…”
Section: Discussionsupporting
confidence: 64%
“…Our findings provide further evidence for the contention that the Great Recession may have adversely affected parents, even if they themselves did not experience economic hardship (Gassman-Pines, Gibson-Davis, & Ananat, 2015). Indeed, our results indicate that widespread economic uncertainty—as measured by the CSI and local unemployment rates—may have increased mothers’ harsh parenting practices.…”
Section: Discussionsupporting
confidence: 64%
“…For example, economic downturns can directly affect the economic well-being of families through poverty, a key predictor of child maltreatment behavior (Kalil 2013). However, community-level economic downturns may also influence child maltreatment indirectly by shaping other community-level factors that can, in turn, affect child maltreatment behavior (Gassman-Pines, Gibson-Davis, and Ananat 2015). For example, such economic downturns can increase strains on social services (Black, McKinnish, and Sanders 2003), increase psychological disorders even for those who remain employed (Catalano et al 2011), and increase demands to financially support members of social networks who lost jobs (Mykyta and Macartney 2011; Gottlieb, Pilkauskas, and Garfinkel 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies rely on repeated cross-sectional data, self-reported anthropometric measurements or a single measure of economic hardship (eg, unemployment). Most prior research uses individual-level employment status, which can be correlated with unobserved traits that also influence health, thus producing misleading associations, and fails to capture changes in spending that occur among families who perceive greater economic uncertainty, but do not actually become unemployed, and among those who have experienced economic hardships, owing to potential losses in investments or a reduction in work hours 10 11. Prior literature is also limited to adults, and few studies have leveraged longitudinal data to compare the same individual to himself or herself over time.…”
Section: Introductionmentioning
confidence: 99%